Antifungal innate immunity in C. elegans - Ewbank, Jonathan (Henry Stewart Talks, 2018)
Ecology of C. elegans, Historical background to host-parasite studies with nematodes, D. coniospora, a natural pathogen of C. elegans, Fungal infection and injury induce antimicrobial peptide genes, Genetics to understand the control of antimicrobial peptide gene expression, The importance of the nematode surface coat, Signal transduction pathways that control antimicrobial peptide gene expression